Bulgaria : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2002)
This paper presents key findings of Bulgaria's Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, and Payment Systems. Bulgaria's macroeconomic policies are tied to three anchors: the discipline imposed by the Currency Board Arrangement; discipline imposed by the accession procedure to the European Union and European Monetary Union; and the conditionalities of IMF and World Bank programs. Although real growth has resumed and the fiscal deficits have been contained, the increasing current account deficit is a matter of concern.